Sejarah dan Strategi Nabi Muhammad.SAW di Mekah - Kori Lilie Muslim; Tomi Hendra (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
Writing about the history of the Prophet Muhammad's Da'wah in Mecca aims to analyze how the propaganda strategy carried out by the Prophet Muhammad in spreading Islam in Mecca. The initial stage through the family of the Prophet and his companions or known as the hiding phase. After the Prophet Muhammad cried out in silence, then the revelation of Allah SWT who ordered the Prophet Muhammad to preach openly. In this bright phase the Prophet Muhammad began to face Quraish kafir racial disturbances. Here we see who the true followers of the Prophet Muhammad and those who just joined in. Weak friends hide their Islam. The Prophet Muhammad secretly preached at the house of Al-Arqam bin Arqam because his house was near the hill of Safa and was a gathering place for many people, so that no one who came to Arqam's house was suspected that there was a meeting there. In addition, Arqam is also a great enemy of the Prophet Muhammad, they have a place of preaching in the heart of the enemy. This is a form of propaganda strategy carried out by the Prophet Muhammad. In the open phase, the Prophet Muhammad and the Muslims began to get harsh treatment, torture and murder. But in the end the Prophet Muhammad was visited by Yathrib, they came to acknowledge that the Prophet Muhammad was the messenger of God even they asked the Prophet Muhammad to be their leader in Yatsrib.